2017
DOI: 10.5296/ijl.v9i2.11051
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Choral Repeated Reading on Foreign Language Reading Fluency of Words in Connected and Disconnected Text

Abstract: Repeated reading has been successfully used to enhance reading fluency in L1, but little is known about how (and to what extent) this strategy impacts reading in foreign language classrooms. Our paper reports the results of a 5-week intervention program aimed to improve reading fluency of middle school students during their English as a foreign language classes. Four classes of sixth-graders divided in two groups received two reading treatments for the last 15 minutes of the class: choral repeated reading (CRR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Çiftçi (2015) found that Turkish EFL learners' reading errors decreased and their comprehension skills improved thanks to the repeated reading method. Some studies have also revealed that repeated and choral reading has a positive effect on the reading fluency and reading comprehension skills of EFL learners (Hocker, 2004;Gorsuch & Taguchi, 2008;Landa, 2009;Roundy & Roundy, 2009;Chang, 2012;Topping, 2014;Dolean et al, 2017). Repeated reading is also based on the Repeated reading method, which involves reading and practicing a text multiple times and then applying it.…”
Section: Discussionmentioning
confidence: 99%
“…Çiftçi (2015) found that Turkish EFL learners' reading errors decreased and their comprehension skills improved thanks to the repeated reading method. Some studies have also revealed that repeated and choral reading has a positive effect on the reading fluency and reading comprehension skills of EFL learners (Hocker, 2004;Gorsuch & Taguchi, 2008;Landa, 2009;Roundy & Roundy, 2009;Chang, 2012;Topping, 2014;Dolean et al, 2017). Repeated reading is also based on the Repeated reading method, which involves reading and practicing a text multiple times and then applying it.…”
Section: Discussionmentioning
confidence: 99%